NILAI NUTRISI JENIS-JENIS TUMBUHAN PAKAN RUSA TIMOR (Cervus timorensis) DI PENANGKARAN BANGSING, PUPUAN, TABANAN, BALI - Indah Adnyani, Desak Putu; Ginantra, I Ketut; Suriani, Ni Luh (SIMBIOSIS, 2017)
This study aims to determine the selection of plants and nutrient content of plant species selected by Timor deer ( Cervus timorensis ). This research was conducted in Penangkaran Bangsing, Pupuan, Tabanan, Bali. Determination of the composition of plant species of Timor deer feed ( C. timorensis ) using the direct method. The species of plants eaten by Timor deer are identified to the species level. The nutrient content of crude protein is determined by Semi-micro Kjeldahl technique, energy content (GE) with Bomb calorimeter , Calcium (Ca) and Phosphorus (P) content by Atomic Absorption Spectrophotometer (ASS) technique. Selection of the plant species eaten using the Ivlev selection index. The nutrient content of plant species is eaten compared to the standard nutrient content for timor deer. The results of the study were 13 species of selected plants, namely Impreata cylindrica, Pennisetum purpureum, Panicum ranusum, Axonopus compressus, Panicum muticum, Spilatnhes paniculata, Mikania micrantha, Gliricidia sepium, Calliandra sp, Hibiscus rosa-sinensis, Sechium edule, Diplazium esculentum, Pogostemon auricularia. The crude protein content ranged from 9.30 - 31.18%, GE 2.724 – 4.446 kcal / g, Ca 0.02 - 0.84%, and P 0.32 to 3.01%. The nutrient content is eaten according to nutritional standards according to Tuckwell (2003).   Keywords : timor deer (Cervus timorensis), selection of plant spesies, nutrient content